Recent updates on the role of microRNAs in prostate cancer - Hassan, Oudai (BioMed Central, 2012)
MicroRNAs (miRNAs) are short non-coding RNAs that are involved in several important biological processes through regulation of genes post-transcriptionally. Carcinogenesis is one of the key biological processes where miRNAs play important role in the regulation of genes. The miRNAs elicit their effects by binding to the 3' untranslated region (3'UTR) of their target mRNAs, leading to the inhibition of translation or the degradation of the mRNA, depending on the degree of complementary base pairing. To-date more than 1,000 miRNAs are postulated to exist, although the field is moving rapidly. Currently, miRNAs are becoming the center of interest in a number of research areas, particularly in oncology, as documented by exponential growth in publications in the last decade. These studies have shown that miRNAs are deregulated in a wide variety of human cancers. Thus, it is reasonable to ask the question whether further understanding on the role of miRNAs could be useful for diagnosis, prognosis and predicting therapeutic response for prostate cancer (PCa). Therefore, in this review article, we will discuss the potential roles of different miRNAs in PCa in order to provide up-to-date information, which is expected to stimulate further research in the field for realizing the benefit of miRNA-targeted therapeutic approach for the treatment of metastatic castrate resistant prostate cancer (mCRPC) in the near future because there is no curative treatment for mCRPC at the moment.